KULTUM SEBAGAI MEDIA DALAM MENSYIARKAN DAKWAH ISLAM MASYARAKAT DUSUN WATU AGUNG DESA DAYAKAN - Siti Saodah (Journal of Islamic Science Community, 2022)
The seven-minute lecture or abbreviated as kultum is a term used in conveying Islamic da'wah which includes advice and warnings related to the teachings of the Islamic religion. The cult method is the most effective way for da'wah actors in general and by students of the Islamic Religious Institute Riyadhlotul Mujahidin KKN Pondok Pesantren Wali Songo in particular, as one of the media in increasing da'wah literacy in Watu Agung Hamlet, Dayakan Village. With this cult media, it is hoped that religious symbols and also public understanding of religious education can increase regularly and consistently. The cult which was held after the dawn prayer and also the tarawih prayer invited a lot of public attention and was an effort for students to interact to establish ukhuwah Islamiyah. The people of Dusun Watu Agung are people who are classified as having minimal knowledge, especially in religious knowledge. The lack of religious literacy and religious activities of the people of Watu Agung Hamlet strongly encourage us as community service participants to share the knowledge gained while studying at the Wali Songo Islamic Boarding School Ngabar Siman, Ponorogo. The author carried out practice and observations during the service and the results showed a very enthusiastic public reaction and also the religious literacy of the majority of the community was more improved. one month has a very significant impact in increasing the da'wah literacy of the people of Watu Agung Hamlet, Dayakan Village, Babadan District, Ponorogo Regen.